Method for preparing metal-organic frameworks with low connectivity and improved thermal stability
Patent Information
- Application Number
- JP2023580408
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-08
- Filing Date
- 2022-06-23
- Publication Date
- 2025-04-22
AI Technical Summary
Metal-organic frameworks (MOFs) with high connectivity suffer from reduced thermal stability due to defects, limiting their effectiveness in high-temperature environments.
A post-synthesis treatment method involving contact with a stabilizing solution containing fluoride ions or acids to enhance the thermal stability of MOFs with defects, maintaining their PXRD pattern and increasing their thermal stability by at least 50°C.
The treated MOFs maintain structural integrity and adsorption capabilities at higher temperatures, effectively stabilizing the framework and enhancing adsorption properties.
Smart Images

Figure 00000024_0000 
Figure 00000024_0001 
Figure 00000024_0002
Abstract
Description
[Technical field]
[0001] (CROSS-REFERENCE TO RELATED APPLICATIONS) This application claims priority to and the benefit of U.S. Provisional Application No. 63 / 317582, filed March 8, 2022, U.S. Provisional Application No. 63 / 296,178, filed January 4, 2022, and U.S. Provisional Application No. 63 / 202856, filed June 28, 2021, which are incorporated by reference in their entireties.
[0002] The present disclosure relates to post-synthesis treatments of metal-organic frameworks to improve their thermal stability. The present disclosure also relates to post-synthesis treatments of metal-organic frameworks to improve CO2 adsorption. The present disclosure further relates to metal-organic frameworks that include non-framework metal cation species. [Background technology]
[0003] The instability of metal-organic frameworks is mitigated by incorporating trivalent metals such as aluminum, chromium, and iron, or tetravalent metals such as zirconium, hafnium, and titanium. As a result, the high degree of connectivity between the metal clusters and the linkers allows the formation of defects without the collapse of the entire structure or loss of chemical stability. These defects can serve as catalytically active sites or as anchoring sites for other elements, and are beneficial for mass and proton transport. However, increasing the amount of defects in a metal-organic framework reduces the thermal stability of the metal-organic framework. Thus, metal-organic frameworks with defects are less useful in higher temperature environments. Summary of the Invention
[0004] Provided herein is a post-synthesis method of thermally stabilizing a metal-organic framework having a plurality of defects, comprising: (a) providing a metal-organic framework; and (b) contacting the metal-organic framework with a stabilizing solution to provide a treated metal-organic framework, wherein the metal-organic framework has a first PXRD pattern and decomposes after about 12 hours at a first temperature, wherein the treated metal-organic framework has a second PXRD pattern substantially the same as the first PXRD pattern, and wherein the treated metal-organic framework is thermally stable at a second temperature at least about 50° C. higher than the first temperature after 12 hours.
[0005] Also provided is a method for producing a metal-organic framework with improved CO2 adsorption, comprising contacting a metal-organic framework with a metal cation and a fluoride ion, e.g., in the form of a metal fluoride, to produce a treated metal-organic framework that includes a non-framework cationic metal species and a fluoride.
[0006] Also provided is a metal-organic framework comprising at least one non-framework cationic metal species selected from the group consisting of lithium, cesium, nickel, cobalt, copper, potassium, silver, and mixtures thereof.
[0007] These and other features and attributes of the disclosed methods and systems, as well as their advantageous applications and / or uses, will become apparent from the following detailed description. [Brief description of the drawings]
[0008] To assist those of ordinary skill in the relevant art in making and using the subject matter herein, reference is made to the accompanying drawings, in which: [Figure 1] 1 shows powder X-ray diffraction patterns of materials made in Examples 1, 2 and 3. [Diagram 2] 1 shows the powder X-ray diffraction pattern of the material prepared in Example 5. [Diagram 3]1 shows the powder X-ray diffraction pattern of the material prepared in Example 6. [Figure 4] 1 shows the powder X-ray diffraction pattern of the material prepared in Example 7. [Diagram 5] 1 shows the powder X-ray diffraction patterns of the materials produced in Examples 9 and 10. [Figure 6] FIG. 13 shows powder X-ray diffraction patterns of UiO-66 samples calcined with and without NH4F, as described in Example 12. [Figure 7] 1 shows powder X-ray diffraction patterns of EMM-71 samples that were first treated with either formic acid or hydrochloric acid and then calcined in the presence of ammonium fluoride from 300° C. to 450° C. in 50° C. increments, as described in Example 13. [Figure 8] 1 shows nitrogen adsorption isotherms for EMM-71 samples treated with a fluoride source and calcined as detailed in Example 13. [Figure 9] Powder X-ray diffraction patterns are shown for EMM-71 samples treated with formic acid or hydrochloric acid (i.e., EMM-71-Formate and EMM-71-HCl in Examples 1 and 2, respectively), and then treated with either ammonium fluoride or ammonium chloride, as detailed in Example 13, and heat-treated at 300° C. for 4 hours. [Figure 10] 1 shows powder X-ray diffraction patterns of EMM-71 samples treated with formic acid and hydrochloric acid (i.e., EMM-71-Formate and EMM-71-HCl from Examples 1 and 2, respectively) and calcined in the presence of different weight percentages of lithium fluoride according to Example 14. [Figure 11] 1 shows density functional theory ("DFT") calculations that represent the total internal energy differences of various acid and decarboxylation products. [Figure 12] FIG. 1 shows powder X-ray diffraction patterns collected at temperatures between 25° C. and 350° C. of EMM-71 samples after treatment with various mixtures (i.e., isobutyric acid (or isobutanoic acid), n-butanoic acid, formic acid, sodium formate, and HCl) as detailed in Example 15. [Figure 13]1 shows powder X-ray diffraction patterns of Zr-Fumarate (the fumarate analogue of UiO-66) before and after NH4F treatment, collected at temperatures between 25° C. and 450° C., as detailed in Example 16. [Figure 14] 1 shows powder X-ray diffraction patterns collected at temperatures between 25° C. and 450° C. of Zr-Fumarate having a fumaric acid to zirconium ratio of 0.91 before and after NH4F treatment, as detailed in Example 16. [Figure 15] 1 shows powder X-ray diffraction patterns of EMM-71 before and after post-synthesis treatment of Example 18 at temperatures ranging from 100° C. to 500° C. [Figure 16] 1 is a plot of a temperature programmed X-ray diffraction experiment of Example 19. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Before the present compounds, components, compositions, and / or methods are disclosed and described, unless otherwise specified, it is to be understood that the disclosure is not limited to particular compounds, components, compositions, reactants, reaction conditions, ligands, catalyst structures, MOF structures, etc., as such may vary. It is also to be understood that the terminology used herein is for the purpose of describing particular embodiments and is not intended to be limiting.
[0010] All numerical values within the detailed description are modified by "about" the stated value to account for experimental error and variations that would be expected by one of ordinary skill in the art.
[0011] As used herein, the term "divalent" refers to the oxidation state of a divalent cation, not whether it is part of an overall charged molecule (e.g., ZnCl2 is dissolved and not dissociated).
[0012] As used herein, the term "valence" refers to the oxidation state of the cation, regardless of whether it is part of an overall charged molecule (i.e., divalent is Zn 2+It can refer to both charged species such as (H2O)6 and neutral compounds such as ZnEt2).
[0013] As described herein, samples were analyzed on either a Panalytical XPert Pro powder X-ray diffractometer fitted with an Anton Paar HTK-16N environmental stage equipped with platinum strip heaters, or a Bruker D8 Endeavor powder X-ray diffractometer. All samples were analyzed as is, without further grinding. All X-ray patterns collected at elevated temperatures were collected during the temperature program ramp described in Example 18 and FIG. 16. Each scan was .about.20 min in the range 2-60° 2θ with a step size of 0.02°. The portion of the temperature program corresponding to the measurements is represented by the dashed line in FIG. 16.
[0014] As used herein, a PXRD pattern is substantially the same as another PXRD pattern if the PXRD patterns have at least five major reflections in common and the peak heights of the major reflections (the most intense in the starting material) do not decrease by more than 50% or the peak widths (measured as half-height widths) do not increase by more than a factor of two.
[0015] The missing reflections in the second PXRD pattern can be due to impurities in the metal-organic framework with the first PXRD pattern. For example, undissolved NHF or other species may be initially present in the powder diffraction pattern, resulting in peaks not observed in the untreated MOF sample. These peaks may disappear upon heating due to volatilization of the species. In this case, the non-MOF components of the mixture are lost, but the peaks representing the framework remain. Alternatively, there are cases where defects are removed by this method. In the case of UiO-66 / EMM-71, the peaks at 4° and 6° 2θ attenuate during calcination after ammonium fluoride treatment. The fact that only these peaks attenuate highlights that they are due to defect structures and not the bulk of the MOF. In general, the disappearance of selective peaks from the pattern can be considered as an indication of the disappearance of defect structures or impurities.
[0016] As used herein, a stabilization solution may be a flow agent, a chemical agent, or a purification agent and may have multiple functions in the stabilization solution.
[0017] As previously described in U.S. Provisional Patent Application No. 63 / 202,856, the EMM-71 metal-organic framework generally has a molecular weight of about 1100 m. 2 / g~2700m 2 / g surface area, porosity of about 0.45 cc / g to 1.1 cc / g, and relative intensity equal to or greater than 0.35. In certain embodiments, these metal-organic frameworks generally have a relative ratio of peak widths at half maximum ((110) reflection to (111) reflection) of less than 3. The relative ratio of peak widths at half maximum is equal to the width of the peak at half height. Additionally, as described herein, EMM-71 metal-organic frameworks may have divalent cations in an amount of 5.0 wt.% or less.
[0018] Metal-organic frameworks ("MOFs") are constructed from three-dimensional assemblies of metal ions (metal clusters) and organic ligands. Metal-organic frameworks contain organic linkers (also called "ligands") that bridge metal nodes (called "secondary building blocks" or "SBUs") through coordination bonds and can self-assemble to form coordination networks. Because the topology can be tuned by equiaxed extension or functionalization of the organic linkers / metal nodes, metal-organic frameworks are customizable for a variety of different uses, from catalytic conversions to biomedical applications. Metal-organic frameworks with their ordered structures and tunability with high pore volumes are suitable for catalysis and batteries, as well as for methods such as gas storage and mass transport, separation (gas adsorption), purification, and heating / cooling.
[0019] The stability of metal-organic frameworks ("MOFs") is due to the strong interactions between ions of similar polarizability (i.e., carboxylates and hard metal cations with high (>3+) valence, or imidazolates and soft metal cations with low (2+) valence). Initially, stable metal-organic frameworks were developed that consisted of trivalent cations, i.e., Al 3+ , Fe 3+ , Cr 3+ The first MOFs were based on phthalic acid derived from Zr 4+ , Hf 4+ , Ti 4+ Other multivalent cations such as ZnO, ZnO, and ZnO-1 have been employed to provide robust frameworks. One exemplary metal-organic framework with multivalent cations is the metal-organic framework UiO-66. Cavka, JH et al., (2008) "A New Zirconium Inorganic Building Brick Forming Metal Organic Frameworks with Exceptional Stability", J. Am. Chem. Soc., v.130(42), pp.13850-13851. At the time of its discovery, UiO-66 had the highest binding affinity of any known metal-organic framework.
[0020] UiO-66 has been synthesized by a variety of synthetic routes, primarily solvothermal. The original metal-organic framework UiO-66 did not have open metal sites inherent in the crystal structure, and the organic ligands did not contain sites for further functionalization. Prior art synthetic conditions include the reaction of zirconium salts (chlorides or oxychlorides) with linear dicarboxylic acids. Early versions of UiO-66 were made with terephthalic acid. Functionalized derivatives and isoreticular analogs (i.e., those composed of longer linear diacids such as 4,4'-biphenyldicarboxylic acid) have resulted. The most common utilized high-boiling aprotic solvents, often N,N-dimethylformamide ("DMF").
[0021] To improve the adsorption and catalytic properties of metal-organic frameworks, defects were incorporated into the metal-organic frameworks during synthesis. The defects are in the form of organic linker defects or node-missing defects, or both. Due to the high connectivity between the metal clusters and the linkers, defects can be formed in high concentrations without collapsing the entire structure. The node-missing defects (removal of clusters) leave mesoscale cavities, providing a more open hierarchical pore structure beneficial for mass and proton transport. Furthermore, the under-coordinated metal ions serve as catalytic active sites or anchoring sites for other active elements. The degree of defects is characterized by comparing the integrated intensity of a large defect area (corresponding to the sum of the integrated intensities of the (100) and (110) reflections) and dividing this integral by the average value of the intensities of the specific reflections (i.e., the (111), (200), and (600) reflections).
[0022] The utility of nodal defects in both adsorption and catalysis applications is considerable. In the case of grafted catalytic sites, defects can be capped with catalytic sites to provide additional functionality. For separation applications, larger defects provide enhanced selectivity for polycyclic naphthene separations and / or selective binding of polycyclic naphthenes by improving diffusion properties. However, defects can affect the mechanical and physical properties of metal-organic frameworks. Thus, during the synthesis of MOFs, in order to maintain well-defined and tunable structures, control of defect formation is essential to achieve the desired MOF properties.
[0023] Furthermore, an increase in defect content in the metal-organic framework can lead to a decrease in thermal stability. For example, to use UiO-66 in high temperature processes, a nearly defect-free material is required. However, this is in conflict with process parameters that require a higher pore volume.
[0024] As described in Examples 12-19 herein, we have discovered that the thermal stability of defective metal-organic frameworks, such as the zirconium metal-organic framework EMM-71 (which may also be described as fully defective UiO-66), is lower than that of non-defective metal-organic frameworks, such as UiO-66. Higher temperature methods require a solution to this problem. As presented herein, the post-synthesis treatment methods of the present invention can improve the thermal stability of defective metal-organic frameworks, such as the Zr-based EMM-71 materials.
[0025] In a first embodiment, the method of the present invention for thermally stabilizing a metal-organic framework is performed post-synthesis. The method includes the steps of: (a) providing a metal-organic framework having a plurality of defects and a first PXRD pattern; and (b) contacting the metal-organic framework with a stabilizing solution to provide a treated metal-organic framework having a second PXRD pattern. As described herein, the metal-organic framework decomposes after about 12 hours at a first temperature. However, the treated metal-organic framework is thermally stable after 12 hours at a second temperature that is at least about 50° C. higher than the first temperature, and the second PXRD pattern is substantially the same as the first PXRD pattern.
[0026] In one embodiment, at least five reflections of the first PXRD pattern are present in the second PXRD pattern, hi one embodiment, the intensities of the reflections of the first PXRD pattern are substantially the same as in the second PXRD pattern.
[0027] In one embodiment, the metal-organic framework has a cubic crystal structure (wherein the structure is referred to as a Bravais lattice type).
[0028] In one embodiment, the metal-organic framework comprises multiple metals selected from aluminum, iron, zirconium, titanium and / or hafnium, and in particular, the metal-organic framework comprises metal nodes of zirconium, titanium and / or hafnium. In one embodiment, the metal-organic framework comprises multiple metals selected from aluminum, iron, zirconium, titanium and / or hafnium. 6-x M x Metal nodes, where M may be hafnium or titanium, or Zr6 metal nodes. In a further embodiment, the metal-organic framework is a zirconium metal-organic framework or a zirconium-based metal-organic framework further comprising hafnium.
[0029] In one embodiment, the metal-organic framework is selected from EMM-71, UiO-66, UiO-67, UiO-68, MOF808, zirconium fumarate, or NU1000, in particular EMM-71.
[0030] In one embodiment, the stabilizing solution comprises fluoride ions. The source of fluoride ions may be selected from the group consisting of, for example, ammonium fluoride and / or alkali metal fluorides, such as lithium fluoride, cesium fluoride, sodium fluoride, potassium fluoride, and mixtures thereof, in particular ammonium fluoride and / or lithium fluoride. Without wishing to be bound by theory, it is believed that the post-treatment with ammonium fluoride provides stability through structural rearrangement, not necessarily through capping of defects with F ions. Indeed, the inventors have noticed that the use of ammonium fluoride results in at least a portion of the defects in the material being lost, improving the overall thermal stability, whereas after post-treatment with alkali metal fluorides, although the stability was improved, no disappearance of the defects was observed. The amount of the source of fluoride ions may range, for example, from about 0.5 to about 50% by weight, for example from about 1 to about 30% by weight, for example about 1, 5, 10, 15 or 20% by weight, relative to the MOF. The amount of fluoride ion may range from about 0.5 to 20 molar equivalents relative to the MOF (assuming the molecular weight of the MOF is 1550 g / mol). Contacting the MOF with the source of fluoride ions may be carried out under any suitable conditions, such as simple contacting at room temperature, or optionally with mixing or stirring or mulling of the mixture (e.g., a slurry), and heating to a calcination temperature, such as 250° C. The contacting period may be any suitable time, such as from 30 seconds to 12 hours, such as from 1 minute or 10 minutes to 1 hour or 2 hours or more.
[0031] In an alternative embodiment, the stabilizing solution comprises at least one acid selected from the group consisting of carboxylic acid, sulfonic acid, sulfuric acid, phosphonic acid, and mixtures thereof, preferably carboxylic acid or sulfuric acid. For example, the carboxylic acid may be selected from formic acid, acetic acid, benzoic acid, propionic acid, butanoic acid, or isobutanoic acid. The sulfonic acid may be selected from methyl sulfonic acid, ethyl sulfonic acid, propyl sulfonic acid, butyl sulfonic acid, or phenyl sulfonic acid. The phosphonic acid may be selected from methyl phosphonic acid, ethyl phosphonic acid, propyl phosphonic acid, butyl phosphonic acid, dimethyl phosphonic acid, diethyl phosphonic acid, dipropyl phosphonic acid, dibutyl phosphonic acid, or diphenyl phosphonic acid. The dialkyl phosphonic acid may also be mixed alkyl groups, such as methyl ethyl phosphonic acid. In a more specific embodiment, the stabilizing solution comprises formic acid, acetic acid, propionic acid, butanoic acid, and / or isobutanoic acid, in particular isobutanoic acid, n-butanoic acid, and / or formic acid, most preferably isobutanoic acid. In one embodiment, the difference in total internal energy (ΔU) between the acid of the organic moiety and the decarboxylation product of the acid of the organic moiety is about 15 U / kcal mol -1 The contact period may be any suitable time, for example, 30 seconds to 12 hours, for example, 1 minute or 10 minutes to 1 hour or 2 hours or more. In this embodiment, the amount of acid may range from about 0.5 to 20 molar equivalents of acid relative to the MOF (assuming a MOF molecular weight of 1550 g / mol). The contact of the metal-organic framework with the acid-containing stabilizing solution may be carried out under any suitable conditions, for example, simple contact at room temperature or optionally with heating up to a calcination temperature such as 250° C., most often at room temperature, optionally with mixing or stirring or kneading of the mixture (e.g., slurry). The contact period may be any suitable time, for example, 30 seconds to 12 hours, for example, 1 minute or 10 minutes to 1 hour or 2 hours or more.
[0032] Isolation of the treated MOFs from the treatment mixture may be carried out by standard means, such as by centrifugation or filtration. The treated MOFs may be further washed by any standard means, for example with water and / or solvents such as methanol, ethanol, and / or acetone.
[0033] In one embodiment, at least a portion of the defects of the MOF are capped or reinforced after treatment. In a further embodiment, the treated metal-organic framework obtained by the method of the first aspect of the present disclosure has at least a portion of its defects capped with an organic moiety selected from at least one of: a carboxylate, such as formate, acetate, benzoate, propionate, butanoate, and / or isobutanoate; a sulfonate, such as methylsulfonate, ethylsulfonate, propylsulfonate, butylsulfonate, and / or phenylsulfonate; and a phosphate, such as dimethylphosphate, diethylphosphate, dipropylphosphate, dibutylphosphate, or diphenylphosphate; and / or the metal-organic framework has at least a portion of its defects capped with an inorganic moiety selected from at least one of: a fluoride, a sulfate (or sulfate), and a bisulfate (or bisulfate).
[0034] As described in Examples 1-11 herein, it has also been found that fluoride-treated metal-organic framework materials can be used to load metal species onto the framework to enhance adsorption properties and provide catalytic effects.
[0035] Accordingly, also herein, in a second aspect, there is provided a method for producing a metal-organic framework with improved CO2 adsorption, comprising contacting a metal-organic framework with a metal cation and a fluoride ion, e.g., in the form of a metal fluoride, to produce a treated metal-organic framework comprising a non-framework cationic metal species and a fluoride.
[0036] In one embodiment, the metal-organic framework has a cubic crystal structure (wherein the structure is referred to as a Bravais lattice type).
[0037] In one embodiment, the metal-organic framework comprises multiple metals selected from aluminum, iron, zirconium, titanium and / or hafnium, in particular the metal-organic framework is zirconium-based, titanium-based and / or hafnium-based. In one embodiment, the metal-organic framework comprises multiple metals selected from aluminum, iron, zirconium, titanium and / or hafnium, in particular zirconium-based, titanium-based and / or hafnium-based. 6-x M x Metal nodes, where M may be hafnium or titanium, or a Zr6 metal node. In further embodiments, the metal-organic framework is a zirconium metal-organic framework or a zirconium-based metal-organic framework further comprising hafnium.
[0038] In one embodiment, the metal-organic framework is selected from EMM-71, UiO-66, UiO-67, UiO-68, MOF808, zirconium fumarate, or NU1000, in particular EMM-71.
[0039] In one embodiment, the source of fluoride ions is selected from ammonium fluoride and / or alkali metal fluorides, such as lithium fluoride, sodium fluoride, cesium fluoride, potassium fluoride, and mixtures thereof. In one embodiment, the metal cations (or cationic metal species) are selected from transition metals, such as nickel, cobalt, copper, and / or silver. In additional or alternative embodiments, the metal cations (or cationic metal species) are selected from alkali metals, such as lithium, sodium, potassium, and / or cesium, preferably potassium and / or cesium. The source of metal cations (or cationic metal species) may be in any suitable form, such as metal chloride, nitrate, and / or fluoride forms. In a particular embodiment, metal fluorides may be used as a source of both fluoride ions and metal cations (or cationic metal species). Suitable examples of such metal fluorides include lithium fluoride, sodium fluoride, potassium fluoride, cesium fluoride, nickel fluoride, silver fluoride, cobalt fluoride, and / or copper fluoride, preferably potassium fluoride, cesium fluoride, nickel fluoride, silver fluoride, cobalt fluoride, and / or copper fluoride, optionally in the presence of ammonium fluoride. Without wishing to be bound by theory, it is believed that fluoride ions induce negative charges on the MOF metal nodes (e.g., Zr-nodes), which allows for the retention of metal cations in the processed MOF.
[0040] In one embodiment, the treated MOFs are synthesized by contacting the metal-organic framework with a solution of metal cations and fluoride ions, thus forming a mixture, in particular a slurry, and optionally heating the mixture to 50° C. or 60° C. The contacting may be carried out under any suitable conditions, optionally under mixing or stirring or kneading. The contacting period may be any suitable time, for example 0 to 16 hours, for example 1 minute to 10 hours, for example about 1 hour or 2 hours. Isolating the treated MOFs from the treatment mixture may be carried out by standard means, such as by centrifugation or filtration. The treated MOFs may be further washed by any standard means, for example with water and / or solvents such as methanol, ethanol, and / or acetone. However, excessive washing should be avoided to prevent washing out of the fluoride and metal cations from the treated MOFs.
[0041] In further embodiments, when contacting occurs, the molar ratio of MOF metal (e.g., Zr) to metal cation in the mixture may range from about 3:4 to 24:1, such as about 2:1 to 6:1. In further embodiments, when contacting occurs, the molar ratio of fluoride ion:metal cation in the mixture may range from about 1:1 to 3:1, such as about 2:1. In all cases, the molecular weight of the MOF is assumed to be 1550 g / mol (e.g., 258.3 g / mol of Zr).
[0042] In one embodiment, the treated metal-organic framework obtained by the method of the second aspect of the present disclosure comprises non-framework cationic metal species in an amount of at least about 0.1, such as at least about 0.15, such as at least about 0.2, even at least about 0.25 or 0.3, and not more than about 0.65, such as not more than about 0.5, such as not more than about 0.4 (i.e., the atomic ratio of non-framework cationic metal species:MOF metal cations (e.g., Cu:Zr, Co:Zr, K:Zr, etc.) as measured by EDX or XRF). In one embodiment, the treated metal-organic framework obtained by the method of the second aspect of the present disclosure comprises fluoride ions in an amount of about 0.1-1, such as about 0.2-0.8, such as about 0.5 or 0.6 (i.e., the atomic ratio of fluoride ions:MOF metal cations (e.g., F:Zr) as measured by EDX or XRF).
[0043] Also provided herein in a third aspect is a modified EMM-71 metal-organic framework, in particular comprising EMM-71 and a moiety selected from the group consisting of formate, acetate, benzoate, propionate, butanoate, isobutanoate, methylsulfonate, ethylsulfonate, propylsulfonate, butylsulfonate, phenylsulfonate, dimethylphosphinate, diethylphosphinate, dipropylphosphinate, dibutylphosphinate, diphenylphosphinate, fluoride, sulfate, or bisulfate, such as fluoride, isobutanoate, butanoate, and / or formate;. Without wishing to be bound by theory, it is believed that at least a portion of the defects of the EMM-71 metal-organic framework are capped or reinforced by said moiety. The modified EMM-71 metal-organic framework may be advantageously obtained by the method of the first aspect of the present disclosure.
[0044] The modified EMM-71 metal-organic framework, in particular the EMM-71 metal-organic framework comprising fluoride moieties, may further comprise a non-framework cationic metal species, in particular lithium, cesium, nickel, cobalt, copper, potassium, silver, and mixtures thereof, selected from, for example, sodium, lithium, cesium, nickel, cobalt, copper, potassium, silver, and mixtures thereof. The cationic metal species may be present, for example, in an amount of at least about 0.1, such as at least about 0.15, for example at least about 0.2, even at least about 0.25 or 0.3, not more than about 0.65, such as not more than about 0.5, for example not more than about 0.4 (i.e., the atomic ratio of non-framework cationic metal species:MOF metal cations (e.g., Cu:Zr, Co:Zr, K:Zr, etc.) as measured by EDX or XRF). The modified EMM-71 metal-organic framework may suitably be obtained by the method of the second aspect of the present disclosure.
[0045] How to make defective zirconium MOFs In the conventional synthesis of zirconium MOFs, linear ditopic ligands are dissolved in a polar aprotic solvent, typically dimethylformamide, along with a zirconium source (i.e., zirconyl chloride or zirconium tetrachloride) and a modifier. The modifier can be a monocarboxylic acid such as formic acid, acetic acid, benzoic acid, or trifluoroacetic acid, but can also be water or hydrochloric acid. Polytopic organic carboxylic acids capable of producing terephthalate linkers (i.e., terephthalic acid) have become ubiquitous in the synthesis of zirconium-based metal-organic frameworks. The original synthesis protocol also included a step of heating the reaction mixture to obtain a polycrystalline powder.
[0046] Depending on the type of modifier used in the synthesis (acetic acid-benzoic acid), the surface area of the metal-organic framework may be tuned. Furthermore, the concentration of modifier has been shown to control the vacancy of the linker. Furthermore, the pKa of the carboxylic acid modifier is believed to be an influential variable as well. Similarly, when very low water content is used to synthesize node-missing UiO-66, as well as methyl- and amino-functionalized analogues, water can effectively create defects.
[0047] To create node missing defects, the inventors have recently developed a new synthetic method to produce metal-organic frameworks with cluster / node missing defects more efficiently than previously known. See U.S. Patent Application No. 63 / 202,856, filed June 28, 2021, entitled "Metal Organic Frameworks Having Node Defects and Methods of Making the Same." As described, the inventors have shown that the inclusion of selected divalent metals not only induces node defects, but that selected divalent metals are capable of inducing the creation of cluster defects to a much greater extent than prior art methodologies. Similar levels of defects have also been demonstrated using concentrated reaction conditions with pre-ligands. See U.S. Patent Application No. 63 / 296,178, filed January 4, 2022, entitled "Method of Making Metal-Organic Frameworks with a Ligand Precursor and Crystallization Aide." As described, the inventors have demonstrated that by this synthetic method, EMM-71 (and functionalized derivatives) can be prepared without the use of divalent metals or amide solvents.
[0048] Beyond the unexpected role of selective divalent metal cations in node-missing defect formation, we observed that the effectiveness of the cations depends on the presence of halide cations in solution, and that the method is reversible by the addition of either HCl or NH4Cl. For example, NH4Br is effective, but the oxidation of the bromide anion to elemental bromine can interfere with the method. Conversely, the addition of ammonium fluoride in the synthesis of metal-organic frameworks does not result in the formation of metal-organic frameworks, because fluoride induces the formation of alternate phases.
[0049] Furthermore, only small amounts of chloride can activate the REO generation mechanism, i.e., the transition from the FCU to the REO topology. Non-halide metal modifiers such as zinc oxide (as well as zinc metal as a source of divalent zinc) effectively generate the transition from the FCU to the REO topology and the REO domains. In the case of zinc oxide, the oxide reacts with acetic acid to produce zinc acetate and water. However, metallic zinc can generate flammable gases, and zinc oxide can affect the acid / base properties of the solution.
[0050] The defect generating cations, measured as M:Zr, appear to be optimal at about 37 wt%. Lower divalent cation ratios, about 25 wt%, are effective in generating REO defects (called clusters of REO topology or node missing defects), especially as measured by powder X-ray diffraction ("PXRD"). Additionally, porosity appears to be maximized at slightly higher values. Attenuated peaks are observed when the divalent cation content is reduced to about 10 wt% relative to zirconium. Excess acetate and high pH can affect the solution process and result in node missing defects.
[0051] In addition to halide concentration, other variables including (1) acetic acid concentration, (2) water content, (3) reaction temperature, (4) metal / ligand ratio, and (5) divalent dopant content can affect the degree of defects in the resulting metal-organic framework material. Water forms zirconium secondary building blocks, but too high a concentration can reduce defect density, creating tensions and necessitating an upper reaction concentration limit. When using hydrated salts, high yields and high defect concentrations are not obtained regardless of water concentration above a certain reaction concentration. This can be improved by using anhydrous salts such as ZrCl4 or by slowly adding zirconium to the reaction medium. For characterization of nanoscale materials, powder X-ray diffraction is described in an editorial published by the American Chemical Society, Holder, CF et al. (2019) "Tutorial on Powder X-ray Diffraction for Characterizing Nanoscale Materials," ACS Nano, v.13(7), pp.7359-7365.
[0052] In addition to acetic acid and water, it was also observed that temperature is an important variable in the synthesis of metal-organic frameworks. Similar to Lillerud's observations, higher temperature reaction conditions tend to produce materials with lower defect content. See Shearer, et al. (2016) "Functionalizing the Defects: Postsynthetic Ligand Exchange in the Metal-Organic Framework Uio-66", Chem. Mater., v.28(20), pp.7190-7193. In that study, reaction conditions were screened between 100°C and 220°C, and materials synthesized at 220°C were nearly defect-free. For metal-organic frameworks with REO topology, the temperature dependence is highlighted. Reactions were performed between 80°C and 130°C, and it was observed that high levels of defects dominated the PXRD patterns only when the reaction was performed between 90°C and 100°C. Below this temperature, there was a large amount of unreacted BDC, and above this temperature, attenuated reflections of the REO domains occurred.
[0053] To remove the pendant ligands and realize the pore volume indicative of the defective structure, the defective MOF may be washed with a slightly basic solution. For example, the MOF may be washed using sodium borate (as opposed to phosphate or carbonate), a weakly interacting anion, and a moderate pH 9 buffer; a significant decrease in peak intensity may be observed.
[0054] Materials washed with formate can increase the measured micropore volume and surface area. However, these results represent a non-optimized washing procedure. Removal of the pendant ligands occurs simultaneously with structural degradation due to the high temperature and high pH conditions of the synthesis.
[0055] As described in detail in U.S. Provisional Application No. 63 / 202,856, filed June 28, 2021, the general steps required to produce a metal-organic framework characterized by a large number of cluster / node missing defects (e.g., EMM-71) include: (a) reacting in a solvent a first metal source (e.g., in the form of a metal precursor, metal complex, or metal oxide) capable of generating tetravalent metal cations in solution, a polytopic organic carboxylic acid capable of generating a terephthalate linker, a second metal source (e.g., in the form of a metal precursor, metal complex, or metal oxide) capable of generating divalent cations in solution, and one or more monocarboxylic acids to provide a reaction solution; (b) heating the reaction solution to a reaction temperature, e.g., of at least 75° C., to provide a reaction mixture; and (c) separating the metal-organic framework material from the reaction mixture. The reaction mixture comprises a metal-organic framework material, and the metal-organic framework material comprises a plurality of metal-organic frameworks. According to this method, metal-organic frameworks each having tetravalent cations and terephthalate linkers are crystallized in a simple cubic lattice (ie, cubic Bravais lattice type).
[0056] In one embodiment, the method for synthesizing defective metal-organic frameworks includes a monocarboxylic acid selected from, for example, formic acid, acetic acid, benzoic acid, difluoroacetic acid, or trifluoroacetic acid. In one embodiment, the monocarboxylic acid concentration is between about 30% and 70% by volume of the total amount of solvent (the total amount of solvent is calculated as the total amount of monocarboxylic acid, organic solvent, and any water present in the reaction solution). Additionally, in one embodiment, the methodology for making defective MOFs includes a molar ratio of tetravalent cation:linker (particularly a terephthalate linker) between about 1.75:1 and about 1:1.75. Also, in one embodiment, the molar ratio of divalent cation / tetravalent cation is between about 0 and about 5. In one embodiment, the reaction solution may further include water at a concentration between about 0 and 5 moles per liter of total reaction volume. In one embodiment, the first metal is selected from zirconium, hafnium, titanium, cerium, or mixtures thereof, such as Zr or a combination of Zr and Hf. In one embodiment, the second metal is selected from Zn, Co, Sn, Cu, or mixtures thereof. In one embodiment, the polytopic organic carboxylic acid is selected from aromatic di-, tri-, or tetracarboxylic acids capable of producing a terephthalate linker. In one embodiment, the polytopic organic carboxylic acid is selected from terephthalic acid or trimesic acid. In one embodiment, the polytopic organic carboxylic acid is functionalized, for example, with an alkyl group, a halo group, a nitro group, a cyano group, an amino group, a sulfonyl group, a thio group, an isocyano group, an alkoxy group, an ether group, an ester group, or a carboxylate group. In one embodiment, the solvent is a polar aprotic solvent, for example, dimethylformamide (DMF).
[0057] In one embodiment, the reaction solution further comprises one or more of F, Cl, Br or I ions, particularly Cl.
[0058] Post-synthesis treatment of zirconium metal-organic frameworks As mentioned above, UiO-66 was first discovered in 2008 and represented a multifaceted change in the development of chemically and thermally stable metal-organic frameworks. At the time of its discovery, the original material (containing a terephthalate linker and a zirconium cation) lacked chemical functionalization. Unlike many other MOFs, in its original form, the metal-organic framework UiO-66 had no open metal sites inherent to its crystal structure, and its organic ligands contained no sites for the addition of functional groups. As mentioned above, syntheses have been developed to create defects in UiO-66 and other zirconium MOFs that provide sites for chemistry and adsorption (open metal sites).
[0059] Moreover, although post-synthetic modifications (post-synthetic exchange of metal cations or ligands) have been successful in providing chemical functionality to UiO-66, they are difficult to apply on a higher scale. Moreover, the use of these techniques to immobilize cationic species relevant for separation and catalysis is laborious, requiring multiple transformations of the base material.
[0060] For example, reactions of unfunctionalized MOF materials with highly reactive species including metal alkyl species such as trimethylaluminum, alkyllithium, and alkyl Grignard reagents have been developed to form sites that can subsequently be metal exchanged. For example, Drake, T. et al. (2018) "Site Isolation in Metal-Organic Frameworks Enables Novel Transition Metal Catalysis," Acc. Chem. Res., v.51, pp. 2129-2138; Ji, P. et al. (2016) "Single-Site Cobalt Catalysts at New Zr8(μ2-O)8(μ2-OH)4Metal-Organic Framework Nodes for Highly Active Hydrogenation of Alkenes, Imines, Carbonyls, and Heterocycles," J. Am. Chem. Soc., v.138, pp. 12234-12242; Zhang, T. et al. (2016) "Metal-Organic Frameworks Stabilize Solution-Inaccessible Cobalt Catalysts for Highly Efficient Broad-Scope Organic Transformations" J. Am. Chem. Soc., v.138, pp.3241-3249; Manna, K. et al. (2016) "Chemoselective single-site Earth-abundant metal catalysts at metal-organic framework nodes," Nat. Commun., v.7, pg. 12610; Manna, K. et al. (2016) "Metal-Organic Framework Nodes Support Single-Site Magnesium-Alkyl Catalysts for Hydroboration and Hydroarnination Reactions," J. Am.Chem. Soc., v.138, pp.7488-7491; Li, Z. et al. (2016) "Sintering-Resistant Single-Site Nickel Catalyst Supported by Metal Organic Framework," J. Am. Chem. Soc., v.138(6), pp. 1977-1982; Ahn, S. et al. (2016) "Stable Metal-Organic Framework-Supported Niobium Catalysts," Inorg. Chem., v.55, pp.11954-11961; Liu, J. et al. (2018) "Beyond the Active Site: Tuning the Activity and Selectivity of a Metal-Organic Framework-Supported Ni Catalyst for Ethylene Dimerization," J. Am. Chem. Soc., v.140(36), pp.11174-11178; Mondloch, J.E. et al. (2013) "Vapor-Phase Metalation by Atomic Layer Deposition in a Metal-Organic Framework," J. Am. Chem. Soc., v.135(28), pp. 10294-10297; Zhang, T. et al. (2016) "Metal-Organic Frameworks Stabilize Solution-Inaccessible Cobalt Catalysts for Highly Efficient Broad-Scope Organic Transformations" J. Am. Chem. Soc., v.138, pp.3241-3249; Kung, C-W. et al.(2015) "Metal-Organic Framework Thin Films as platformss for Atomic Layer Deposition of Cobalt Ions To Enable Electrocatalytic Water Oxidation," ACS Appl. Interfaces, v.7(51), pp.28223-28230; Ahn, S. et al. (2018) "Pushing the Limits on Metal-Organic Frameworks as a Catalyst Support:NU-1000 Supported Tungsten Catalysts for o-Xylene Isomerization and Disproportionation,"J. Am. Chem. Soc. Soc., v.140(27), pp.8535-8543; Platero-Prats, A. et al. (2017) "Bridging Zirconia Nodes within a Metal-Organic Framework via Catalytic Ni-Hydroxo Clusters to Form Heterobimetallic Nanowires," J. Am. Chem. Soc., v.139(30), pp.10410-10418; and Peters, AW et al. (2015) "Atomically Precise Growth of Catalytically Active Cobalt Sulfide on Flat Surfaces and within a Metal-Organic Framework via Atomic Layer Deposition," ACS Nano, v.9(8), pp.8484-8490. Alternatively, metals can be incorporated into the zirconium secondary building blocks in dimethylformamide. Yuan, S. et al.(2015) "Cooperative Cluster Metalation and Ligand Migration in Zirconium Metal-Organic Frameworks," Angew Chemie Int. Ed., v.54(49), pp. 14696-14700. However, this effect was not demonstrated in water, which is expected to hinder the metal incorporation process. For example, Abdel-Mageed, AM, et al. (2019) "Highly Active and Stable Single-Atom Cu Catalysts Supported by a Metal-Organic Framework," J. Am. Chem. Soc., v.141(13), pp.5201-5210. .
[0061] Fluoride incorporation into zirconium MOFs has been performed. Lin, KY A. et al. (2016) "Adsorption of fluoride to Uio-66-NH2in Water: Stability, Kinetic, Isotherm and Thermodynamic Studies," J. Col. Inter Sci., v.461, pp.79-87; Zhao, X. et al. (2014) "The Stability and Defluoridation Performance of MOFs in Fluoride Solutions," Micro. Meso. Mater., v.185, pp.72-78; Prabhu, SM et al. (2021) "Synthesis and Characterization of Defective Uio-66 for Efficient Co-immobilization of Arsenate and Fluoride from Single / Binary Solutions" Environ. Poll., v.278, pg.116841. However, the ability of these fluoride materials to adsorb cations has not been explored until now. The inventors have discovered that fluoride-treated materials can support metal species onto the framework, enhancing their adsorption properties and imparting catalytic effects.
[0062] The aspects of the present disclosure will be described in more detail by specific examples.The following examples are provided for illustrative purposes and are not intended to limit the present disclosure in any manner.Those skilled in the art in the relevant technical field will easily recognize that various parameters can be changed or modified to obtain essentially the same results.The following non-limiting examples are provided to illustrate the present disclosure. EXAMPLES
[0063] Samples were analyzed in the 2θ range of 2–60° using either a Panalytical XPert Pro powder X-ray diffractometer fitted with an Anton Parr HTK‐16N environmental stage equipped with platinum strip heaters, or a Bruker D8 Envdevor instrument in continuous mode using copper Kα radiation, Bragg‐Bentano geometry, equipped with a Lynxeye detector. In both cases, interplanar spacing (d‐spacing) was calculated in angstroms. Intensities were not corrected for Lorentz and polarization effects. The positions of the diffraction peaks in 2θ, and the relative peak area intensities of the lines, I / I(o), where Io is the intensity of the line stronger than the background, were determined with the MDI Jade peak fitting algorithm using a third order polynomial background fit. It should be understood that diffraction data described as single lines may, under certain conditions, such as differences in crystallographic alterations, consist of multiple overlapping lines that appear as resolved or partially resolved lines. Typically, crystallographic changes include minor changes in unit cell parameters and / or changes in crystal symmetry, without altering framework connectivity. These minor effects, including changes in relative intensity, may also result from differences in cation content, framework composition, nature and degree of pore filling, crystal size and shape, preferred orientation, and thermal and / or hydrothermal history. All samples were analyzed as is, without further polishing. All X-ray diffraction patterns collected at elevated temperatures were collected during the programmed temperature ramp described in Example 18 and Figure 16. Each scan was ∼20 min in the range 2-60° 2θ with a step size of 0.02°. The portions of the temperature program corresponding to the measurements are represented in Figure 16 as dashed lines.
[0064] Atomic ratios were collected by energy dispersive X-ray (EDX) using a Thermo Fisher Apreo 2 S HiVac equipped with two Oxford Ultim Max170 EDS detectors and processed with Oxford Aztec software. Samples were analyzed at 5 or 15 keV with currents ranging from 0.2 to 0.8 nA, or by X-ray fluorescence (XRF) using a Burker S8 Tiger X-ray fluorescence instrument using a Rh X-ray tube operated at 3 kW (60 kV, 150 mA) in wavelength dispersive XRF mode.
[0065] Gravimetric CO2 uptake (adsorption and adsorption capacity) was measured using a Mettler Toledo TGA / DSC1 thermogravimetric analyzer at 1 bar 85 / 15 CO2 / N2. Prior to the measurements, the samples were outgassed in the analyzer under a nitrogen stream at 140°C. The samples were then cooled to 35°C and the gas was switched to a 1 bar 85 / 15 CO2 / N2 mixture.
[0066] As shown in Examples 1-11 below, in support of the method of the first aspect of the present disclosure, the adsorption of fluoride species onto a zirconium metal-organic framework was utilized to enable the adsorption of metal species relevant to adsorption and catalysis applications.
[0067] The following Examples 12-19 illustrate the thermal stabilization of zirconium metal-organic frameworks in support of the method of the second aspect of the present disclosure.
[0068] Example 1: Synthesis of EMM-71-Formate Metal-organic framework EMM-71 was synthesized by the method described in 63 / 202,856 or 63 / 296,178. EMM-71 was then suspended in 0.25 M sodium formate to give a 10 wt% MOF suspension (e.g., 10 grams ("g") of formate solution per gram of EMM-7). The solution was heated to 100°C for 30 minutes, then filtered and the filter cake was washed with 1 vol% formic acid solution (equivalent to the initial sodium formate solution). The filter cake was then rinsed with acetone to remove water and air-dried. This dry powder corresponds to EMM-71 with defects capped with formate and is referred to as EMM-71-Formate. Figure 1 shows the powder X-ray diffraction patterns of the materials produced in Examples 1, 2 and 3.
[0069] Example 2: Synthesis of EMM-71-HCl EMM-71-Formate from Example 1 was weighed and added to a beaker. 1% by volume HCl solution was added to the beaker to create a 10% by weight slurry. This slurry was stirred at room temperature for 30-90 minutes and then filtered. The filter cake was then washed with at least 3 volume equivalents (relative to the volume of the initial MOF / HCl slurry) of water. The filter cake was then washed with acetone to displace the water and dried. The HCl wash exposes all defects. The resulting powder is EMM-71-HCl (see PXRD pattern in Figure 1).
[0070] Example 3: Synthesis of EMM-71-Fluoride (EMM-71-F) EMM-71-Formate from Example 1 or EMM-71-HCl from Example 2 was removed in chunks in a container and suspended in water to make a 10 wt% slurry. To this was added sodium fluoride (10 wt% relative to MOF). The mixture was stirred and heated (35°C-50°C) for 90 minutes. The mixture was then filtered and washed with 3 volume equivalents of water relative to the initial slurry volume. The resulting powder is EMM-71-F (see PXRD pattern in Figure 1).
[0071] Example 4: Treatment of EMM-71-HCl with copper chloride dihydrate or cobalt chloride (anhydrous) 500 mg of EMM-71-HCl from Example 2 was suspended in 10 mL of water. Either 250 mg of copper chloride dehydrate or 187 mg of cobalt chloride (anhydrous) was added to the mixture and stirred at 50° C. The mixture was filtered and washed with 2 volume equivalents of water followed by acetone. The filter cake was dried.
[0072] Example 5: Treatment of EMM-71-HCl with copper fluoride hydrate, cobalt fluoride, or nickel fluoride in the presence of ammonium fluoride 500 mg of EMM-71-HCl from Example 2 was suspended in 5 mL of deionized water and either 100 mg or 200 mg of copper fluoride dihydrate, 70 mg or 140 mg of cobalt fluoride, or 220 mg of nickel fluoride was added along with 100 mg of ammonium fluoride. The mixture was stirred at 50° C. for 90 minutes, then filtered and washed with water and then with acetone. FIG. 2 shows the powder X-ray diffraction pattern of the material produced in Example 5.
[0073] Example 6: Treatment of EMM-71-HCl with copper chloride dihydrate or cobalt chloride (anhydrous) and ammonium fluoride 1,000 mg of EMM-71-HCl from Example 2 was suspended in 10 mL of deionized water and 250 mg of copper chloride dihydrate was added along with 100-150 mg of ammonium fluoride. The mixture was then heated to 50° C. for 90 minutes, filtered, and washed with water and then with acetone.
[0074] 2 g of EMM-71-HCl from Example 2 was suspended in 20 mL of deionized water and 330 mg of cobalt chloride was added along with 420 mg of ammonium fluoride. The mixture was then heated to 50° C. for 90 minutes, filtered, washed with water and then with acetone.
[0075] FIG. 3 shows the powder X-ray diffraction pattern of the material prepared in Example 6.
[0076] Example 7: Treatment of EMM-71-F with metal chlorides in the presence of ammonium fluoride 500 mg of EMM-71-F from Example 3 was suspended in 5 mL of water with 50 mg of ammonium fluoride. Either 82 mg of cobalt chloride (anhydrous), 109 mg of copper chloride dihydrate, or 305 mg of nickel chloride hexahydrate was added. The reaction mixture was stirred at 50° C. for 90 minutes, then filtered, washed with water, acetone, and air-dried. FIG. 4 shows the powder X-ray diffraction pattern of the material produced in Example 7.
[0077] Example 8: Treatment of EMM-71-F with metal salts in the absence of fluoride 500 mg of EMM-71-F from Example 3 was suspended in 5 mL of water. Either 82 mg of cobalt chloride (anhydrous), 109 mg of copper chloride dihydrate, 305 mg of nickel chloride hexahydrate, or 135 mg of silver nitrate was added. The reaction mixture was stirred at 50°C for 90 min, then filtered, washed with water, acetone, and air-dried. For the silver samples, the reactions were protected from light. These results indicate that even if the MOFs are pre-fluorinated, only limited amounts of metals other than silver are adsorbed unless additional fluorine is added during treatment with the metal salts (see Table 1).
[0078] Example 9: Treatment of EMM-71-HCl with an alkali metal fluoride salt 6 g of EMM-71-HCl from Example 2 was suspended in 40 mL of water and either 1.12 g of potassium fluoride or 1.47 g of cesium fluoride was added to the mixture. The mixture was heated to 50° C. and stirred for 90 minutes. The solid was filtered off and washed with 10 mL of deionized water. The water was then exchanged with acetone and the filter cake was dried. FIG. 5 shows the powder X-ray diffraction pattern of the material produced in Example 9.
[0079] Example 10: Treatment of EMM-71-Formate with Alkali Metal Fluoride Salts 500 mg of EMM-71-Formate from Example 1 was suspended in 5 mL of water and 50-200 mg of cesium fluoride was added to the reaction mixture and heated to 50° C. for 90 minutes. The solid was filtered off and washed with 10 mL of deionized water. The water was then exchanged with acetone and the filter cake was dried. FIG. 5 further shows the powder X-ray diffraction pattern of the material produced in Example 10.
[0080] Example 11: Gravimetric CO 2 Absorption measurement Samples of Examples 1, 2, 9 and 10 herein were outgassed in a thermogravimetric analyzer under a N2 stream at 140° C. The samples were then cooled to 35° C. and the gas was switched to an 85 / 15 mixture of CO2 / N2 at 1 bar.
[0081] Table 1 below shows the atomic ratios collected by EDX (ratios for Examples 1, 2, 3, 4, 5, 6 and 7) and XRF (ratios for Examples 8 and 9). TIFF2024526235000001.tif185123
[0082] Table 2 below shows the gravimetric CO2 adsorption capacity measured at 1 bar for 85 / 15 CO2 / N2. TIFF2024526235000002.tif78158
[0083] Example 12: Thermal stabilization of UiO-66 by ammonium fluoride treatment A 300 mg sample of UiO-66 was agglomerated, suspended in 1 mL of aqueous solution containing 30 mg of ammonium fluoride, and mixed briefly to homogenize. The sample was then calcined at temperatures between 350 and 500 °C and compared with an untreated UiO-66 sample. - The sample calcined in the presence of NHF maintained its PXRD pattern at a temperature of 450 °C, indicating higher thermal stability, in comparison to the untreated material, which loses crystallinity completely at a temperature of 400 °C. Figure 6 shows the powder X-ray diffraction patterns of UiO-66 samples calcined with and without treatment with NHF at 400 and 500 °C.
[0084] Example 13: Defect removal and thermal stabilization of EMM-71 by ammonium fluoride treatment A 300 mg sample of EMM-71 (EMM-71-Formate from Example 1 or EMM-71-HCl from Example 2) was agglomerated and suspended in 1 mL of aqueous solution containing 30 mg of ammonium fluoride and mixed briefly to homogenize. The sample was then calcined at temperatures ranging from 300 to 500 °C. Samples calcined in the presence of F showed higher thermal stability while maintaining the PXRD pattern at a temperature of 450 °C. This is in comparison to the untreated material, which shows a complete loss of crystallinity at a temperature of 300 °C. Figure 7 shows the powder X-ray diffraction patterns of EMM-71 samples treated with either formic acid (i.e., EMM-71-Formate from Example 1) or hydrochloric acid (i.e., EMM-71-HCl from Example 2) and calcined in the presence of ammonium fluoride at temperatures ranging from 300 °C to 450 °C in 50 °C increments. Figure 8 shows the nitrogen adsorption isotherms of EMM-71 samples treated with an ammonium fluoride source and calcined. FIG. 9 shows the powder X-ray diffraction patterns of EMM-71-Formate and EMM-71-HCl samples (from Examples 1 and 2, respectively) treated with ammonium fluoride or ammonium chloride and heat treated at 300° C. for 4 hours.
[0085] Example 14: Thermal stabilization of EMM-71 with limited defect removal by lithium fluoride treatment A 300 mg sample of EMM-71 (EMM-71-Formate from Example 1 or EMM-71-HCl from Example 2) was agglomerated and suspended in 2 mL of water with 15, 30 or 45 mg of lithium fluoride. The sample was stirred at 80° C. for 1 hour, then ramped for four hours (4 hr) and calcined at 350° C. for 12 hours in air. The sample exhibited a powder X-ray diffraction pattern that still contained clear peaks at 4° and 6° 2θ, indicating that defects remained. FIG. 10 shows the powder X-ray diffraction patterns of formic acid and hydrochloric acid treated EMM-71 samples (i.e., EMM-71-Formate from Example 1 and EMM-71-HCl from Example 2, respectively) calcined in the presence of different weight percent lithium fluoride.
[0086] Example 15: Thermal stabilization of EMM-71 with limited defect removal by isobutyric acid treatment Defects capped with organic moieties can also be robust against thermal degradation. The thermal stability limit is associated with the intrinsic thermal stability of the organic moiety. Density functional theory (DFT) modeling predicted that isobutanoic acid exhibits superior thermal stability compared to other organic acids. Isobutanoic acid can be added in several ways. A sample of EMM-71 can be suspended in an aqueous solution of isobutanoic acid (~0.25 M) with stirring, optionally heated, and then isolated by filtration. Alternatively, EMM-71 can be mixed with a solution of isobutanoic acid (sufficient water to create a slurry and 234 μL / g of MOF) and calcined to obtain a thermally stable material. Figure 11 shows density functional theory ("DFT") calculations showing the difference in total internal energy of various acids and the decarboxylation product. FIG. 12 shows the powder X-ray diffraction patterns of EMM-71 samples after washing with various mixtures (i.e., isobutyric acid (or isobutanoic acid), n-butanoic acid, formic acid, sodium formate, and HCl); the patterns were collected at temperatures between 25° C. and 350° C. The results show the following stabilization efficiency: isobutyric acid (i-BuCO2H)>n-butanoic acid (n-BuCO2H)~formic acid>sodium formate>HCl.
[0087] Example 16: Thermal stabilization of a commercial sample of Zr-fumarate by ammonium fluoride treatment This example illustrates the NH4F treatment of zirconium fumarate (the fumarate analog of UiO-66). Zirconium fumarate samples were purchased from Strem Chemical with Zr-to-fumaric acid molar ratios ranging from 0.68 to 0.92 (Strem Product No. 40-1114) and 0.91 (Strem Product No. 40-1106), respectively. Zr-fumaric acid was mixed with ammonium fluoride and 10% by weight of NH4F relative to the MOF. Minimal water was added, the mixture was stirred, and dried at 100°C. Powder X-ray diffraction patterns of Zr-fumarates (the fumarate analog of UiO-66) with zirconium to fumaric acid molar ratios ranging from 0.68 to 0.92 before and after NH4F treatment are shown in Figure 13; the patterns were collected at temperatures ranging from 25°C to 450°C. The powder X-ray diffraction patterns of Zr fumarate having a fumaric acid to zirconium molar ratio of 0.91 before and after NH4F treatment; the patterns were collected at temperatures between 25° C. and 450° C.; are shown in FIG.
[0088] Example 17: Calculation of ΔU using Dmol3 Molecular models were generated for the starting carboxylic acid, the resulting carbon dioxide (or carbon monoxide in the case of formic acid), and the resulting alkane (or water in the case of formic acid). For the calculation of the alkane and CO2, both molecules were put into the same model and calculated spaced apart so that interactions were not included in the calculation.
[0089] Example 18: Thermal stabilization of MOFs by sulfuric acid treatment 5 g of EMM-71 was weighed out and slurried with 50 mL of water. 500 mg or 1,000 mg of concentrated sulfuric acid (resulting in a 10 or 20 wt % H2SO4 solution) was added and the mixture was stirred at room temperature for 2 h. The mixture was then filtered and washed with methanol (or alternatively ethanol, acetone, and / or water). The isolated solid was dried at 100 °C-150 °C. Figure 15 shows the powder X-ray diffraction patterns collected for samples of EMM-71 before (black) and after (gray) treatment. The temperatures correspond to the temperature programmed PXRD experiments detailed in Example 19.
[0090] Example 19: Temperature Programmed Powder X-ray Diffraction Samples were analyzed on a Panalytical XPert Pro powder X-ray diffractometer fitted with an Anton Paar HTK-16N environmental stage equipped with platinum strip heaters. Samples were processed according to the temperature program shown in Figure 16. Figure 16 is a plot of a temperature programmed X-ray diffraction experiment. The black lines represent the ramp or hold times. The dashed lines represent the times when the diffraction patterns were collected.
[0091] Numerous changes, modifications, and variations will be apparent to those skilled in the art in light of the foregoing description without departing from the spirit or scope of the present disclosure, and where numerical lower limits and numerical upper limits are listed herein, ranges from any lower limit to any upper limit are contemplated.
[0092] Additional Embodiments Additionally or alternatively, the present invention relates to:
[0093] EMBODIMENT 1 (a) providing a metal-organic framework; and (b) contacting the metal-organic framework with a stabilization solution to provide a treated metal-organic framework. Including, the metal-organic framework has a first PXRD pattern and decomposes after about 12 hours at a first temperature; 16. A method of thermally stabilizing a metal-organic framework having a plurality of defects, wherein the treated metal-organic framework has a second PXRD pattern substantially the same as the first PXRD pattern, and the treated metal-organic framework is thermally stable at a second temperature at least about 50° C. higher than the first temperature after 12 hours.
[0094] EMBODIMENT 2 2. The method of embodiment 1, wherein the stabilizing solution comprises fluoride ions, in particular the source of fluoride ions is selected from the group consisting of ammonium fluoride, lithium fluoride, cesium fluoride, sodium fluoride, potassium fluoride, and mixtures thereof, preferably ammonium fluoride and / or lithium fluoride, more preferably ammonium fluoride.
[0095] EMBODIMENT 3 3. The method of embodiment 2, wherein the amount of fluoride ions is in the range of about 0.5-20 molar equivalents relative to the metal-organic framework, and / or the amount of the source of fluoride ions is in the range of about 0.5-50 wt.%, preferably about 1-30 wt.%, relative to the metal-organic framework.
[0096] EMBODIMENT 4 2. The method of embodiment 1, wherein the stabilizing solution comprises an acid selected from the group consisting of carboxylic acids, sulfonic acids, sulfuric acids, phosphonic acids, and mixtures thereof, preferably carboxylic acids or sulfuric acids.
[0097] EMBODIMENT 5 5. The method of embodiment 4, wherein the stabilization solution comprises a carboxylic acid selected from the group consisting of formic acid, acetic acid, propionic acid, butanoic acid, isobutanoic acid, and mixtures thereof, preferably isobutanoic acid, n-butanoic acid, and / or formic acid, more preferably isobutanoic acid.
[0098] EMBODIMENT 6 6. The method of embodiment 4 or 5, wherein the amount of acid ranges from about 0.5 to 20 molar equivalents relative to the metal-organic framework.
[0099] EMBODIMENT 7 The method of any one of the preceding embodiments, wherein at least five reflections of the first PXRD pattern are present in the second PXRD pattern.
[0100] EMBODIMENT 8 8. The method of any one of the preceding embodiments, wherein the intensity of the reflections in the first PXRD pattern is substantially the same as the intensity of the reflections in the second PXRD pattern. 7. The method according to any one of embodiments 1 to 6.
[0101] EMBODIMENT 9 A method for producing a metal-organic framework having improved CO2 adsorption, comprising contacting a metal-organic framework with a metal cation and a fluoride ion to produce a treated metal-organic framework comprising a non-framework cationic metal species and a fluoride.
[0102] EMBODIMENT 10 10. The method of embodiment 9, wherein the source of fluoride ions is selected from the group consisting of ammonium fluoride, lithium fluoride, sodium fluoride, cesium fluoride, potassium fluoride, and mixtures thereof.
[0103] EMBODIMENT 11 11. The method of embodiment 9 or 10, wherein the cationic metal species is a transition metal or an alkali metal.
[0104] EMBODIMENT 12 12. The method of any one of embodiments 9-11, wherein the cationic metal species is selected from the group consisting of lithium, sodium, cesium, nickel, cobalt, copper, potassium, and / or silver.
[0105] EMBODIMENT 13 13. The method of any one of embodiments 9 to 12, wherein a metal fluoride is used as a source of fluoride ions and cationic metal species.
[0106] EMBODIMENT 14 14. The method of embodiment 13, wherein the metal fluoride is selected from the group consisting of lithium fluoride, sodium fluoride, potassium fluoride, cesium fluoride, nickel fluoride, silver fluoride, cobalt fluoride, copper fluoride, and mixtures thereof, preferably potassium fluoride, cesium fluoride, nickel fluoride, silver fluoride, cobalt fluoride and / or copper fluoride.
[0107] EMBODIMENT 15 15. The method of embodiment 13 or 14, further comprising contacting with ammonium fluoride.
[0108] EMBODIMENT 16 16. The method of any one of embodiments 9 to 15, wherein the molar ratio of MOF metal:cationic metal species in the mixture is in the range of about 3:4 to 24:1, preferably about 2:1 to 6:1.
[0109] EMBODIMENT 17 17. The method of any one of embodiments 9 to 16, wherein the molar ratio of fluoride ions to cationic metal species in the mixture is in the range of about 1:1 to 3:1.
[0110] EMBODIMENT 18 18. The method according to any one of the preceding embodiments, wherein the metal-organic framework comprises multiple metals selected from aluminum, iron, zirconium, titanium and / or hafnium, preferably multiple metals selected from zirconium, titanium and / or hafnium.
[0111] EMBODIMENT 19 19. The method of any one of the preceding claims, wherein the metal-organic framework comprises zirconium, titanium and / or hafnium metal nodes.
[0112] EMBODIMENT 20 20. The method of any one of the preceding embodiments, wherein the metal-organic framework is a zirconium-based metal-organic framework, optionally further comprising hafnium and / or titanium, preferably a zirconium-based or zirconium and hafnium-based metal-organic framework.
[0113] EMBODIMENT 21 21. The method of any one of the preceding claims, wherein the metal-organic framework comprises a Zr6 metal node.
[0114] EMBODIMENT 22 22. The method of any one of the preceding claims, wherein the metal-organic framework has a cubic unit cell.
[0115] EMBODIMENT 23 23. The method according to any one of the preceding embodiments, wherein the metal-organic framework is selected from EMM-71, UiO-66, UiO-67, UiO-68, MOF808, zirconium fumarate, or Nu1000, preferably EMM-71.
[0116] EMBODIMENT 24 EMM-71 and a moiety selected from the group consisting of formate, acetate, benzoate, propionate, butanoate, isobutanoate, methylsulfonate, ethylsulfonate, propylsulfonate, butylsulfonate, and / or phenylsulfonate, dimethylphosphate, diethylphosphate, dipropylphosphate, dibutylphosphate, diphenylphosphate, fluoride, sulfate, or bisulfate, preferably fluoride, isobutanoate, butanoate, and / or formate; Metal-organic frameworks, including:
[0117] EMBODIMENT 25 25. The metal-organic framework of embodiment 24, wherein the EMM-71 is a Zr-based EMM-71.
[0118] EMBODIMENT 26 A metal-organic framework according to embodiment 24 or 25, obtainable by the method according to any one of embodiments 1 to 8 and 16 to 23.
[0119] EMBODIMENT 27 27. The metal-organic framework according to any one of embodiments 24 to 26, comprising a fluoride.
[0120] EMBODIMENT 28 28. The metal-organic framework of any one of embodiments 24 to 27, further comprising at least one non-framework cationic metal species selected from the group consisting of sodium, lithium, cesium, nickel, cobalt, copper, potassium, silver, and mixtures thereof.
[0121] EMBODIMENT 29 29. The metal-organic framework of embodiment 28, wherein the non-framework cationic metal species is present in an amount, calculated as the atomic ratio of non-framework cationic metal species to MOF metal cation, of at least 0.1, preferably from about 0.1 to 0.65, more preferably from about 0.2 to 0.5.
[0122] EMBODIMENT 30 30. A metal-organic framework according to embodiment 28 or 29, obtainable by the method according to any one of embodiments 9 to 23.
Claims
1. (a) providing a metal-organic framework; and (b) contacting the metal-organic framework with a stabilization solution to provide a treated metal-organic framework. Including, the metal-organic framework has a first PXRD pattern and decomposes after about 12 hours at a first temperature; A method of thermally stabilizing a metal-organic framework having a plurality of defects, wherein the treated metal-organic framework has a second PXRD pattern substantially the same as the first PXRD pattern, and the treated metal-organic framework is thermally stable at a second temperature at least about 50° C. higher than the first temperature after 12 hours.
2. 10. The method of claim 1, wherein the stabilization solution comprises a source of fluoride ions selected from the group consisting of ammonium fluoride, lithium fluoride, cesium fluoride, sodium fluoride, potassium fluoride, and mixtures thereof.
3. The method of claim 2, wherein the amount of fluoride ion ranges from about 0.5 to 20 molar equivalents relative to the metal-organic framework.
4. 2. The method of claim 1, wherein the stabilizing solution comprises an acid selected from the group consisting of carboxylic acids, sulfonic acids, sulfuric acids, phosphonic acids, and mixtures thereof, preferably carboxylic acids or sulfuric acids.
5. 5. The method of claim 4, wherein the stabilization solution comprises a carboxylic acid selected from the group consisting of formic acid, acetic acid, propionic acid, butanoic acid, isobutanoic acid, and mixtures thereof.
6. The method of claim 4, wherein the amount of the acid ranges from about 0.5 to 20 molar equivalents relative to the metal-organic framework.
7. 2. The method of claim 1, wherein at least five reflections of the first PXRD pattern are present in the second PXRD pattern, and preferably the intensities of the reflections of the first PXRD pattern are substantially the same as the intensities of the reflections of the second PXRD pattern.
8. contacting the metal-organic framework with metal cations and fluoride ions to produce a treated metal-organic framework comprising non-framework cationic metal species and fluoride. 2 Method for the preparation of metal-organic frameworks with improved adsorption.
9. 9. The method of claim 8, wherein the source of fluoride ions is selected from the group consisting of ammonium fluoride, lithium fluoride, sodium fluoride, cesium fluoride, potassium fluoride, and mixtures thereof.
10. The method of claim 8 , wherein the cationic metal species is a transition metal or an alkali metal.
11. 11. The method of claim 10, wherein the cationic metal species is selected from the group consisting of lithium, sodium, cesium, nickel, cobalt, copper, potassium, and / or silver.
12. The method of claim 8, wherein a metal fluoride is used as a source of fluoride ions and cationic metal species.
13. 13. The method according to claim 12, wherein the metal fluoride is selected from the group consisting of lithium fluoride, sodium fluoride, potassium fluoride, cesium fluoride, nickel fluoride, silver fluoride, cobalt fluoride, copper fluoride, and mixtures thereof, preferably potassium fluoride, cesium fluoride, nickel fluoride, silver fluoride, cobalt fluoride and / or copper fluoride.
14. 13. The method of claim 12 further comprising contacting with ammonium fluoride.
15. 9. The process of claim 8, wherein the molar ratio of MOF metal to cationic metal species in the mixture ranges from about 3:4 to 24:1, preferably from about 2:1 to 6:
1.
16. 9. The method of claim 8, wherein the molar ratio of fluoride ions to cationic metal species in the mixture ranges from about 1:1 to 3:
1.
17. 9. The method of claim 1 or 8, wherein the metal-organic framework comprises a plurality of metals selected from aluminum, iron, zirconium, titanium and / or hafnium.
18. 9. The method of claim 1 or 8, wherein the metal-organic framework comprises metal nodes of zirconium, titanium and / or hafnium, preferably the metal-organic framework is a zirconium-based metal-organic framework, optionally further comprising hafnium and / or titanium.
19. 9. The method of claim 1 or 8, wherein the metal-organic framework is selected from EMM-71, UiO-66, UiO-67, UiO-68, MOF808, zirconium fumarate, or Nu1000, preferably EMM-71.
20. EMM-71 and a moiety selected from the group consisting of formate, acetate, benzoate, propionate, butanoate, isobutanoate, methylsulfonate, ethylsulfonate, propylsulfonate, butylsulfonate, and / or phenylsulfonate, dimethylphosphate, diethylphosphate, dipropylphosphate, dibutylphosphate, diphenylphosphate, fluoride, sulfate, or bisulfate, preferably fluoride, isobutanoate, butanoate, and / or formate; Metal-organic frameworks, including:
21. 21. The metal-organic framework of claim 20, obtainable by the method of claim 1.
22. 21. The metal-organic framework of claim 20 comprising a fluoride.
23. 21. The metal-organic framework of claim 20, further comprising at least one non-framework cationic metal species selected from the group consisting of sodium, lithium, cesium, nickel, cobalt, copper, potassium, silver, and mixtures thereof.
24. 24. The metal-organic framework of claim 23, wherein the non-framework cationic metal species is present in an amount, calculated as an atomic ratio of non-framework cationic metal species to MOF metal cations, of at least 0.
1.
25. 24. The metal-organic framework of claim 23, obtainable by the method of claim 8. [others] This amendment changed the dependent claim numbers of claims 6-7, 10-12, 14-19, 21-23 and 25 before the amendment.